The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1093/ilar.51.4.310
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Quail as a Model System for Studying the Neuroendocrine Control of Reproductive and Social Behaviors

Abstract: Japanese quail (Coturnix japonica; referred to simply as quail in this article) readily exhibit sexual behavior and related social behaviors in captive conditions and have therefore proven valuable for studies of how early social experience can shape adult mate preference and sexual behavior. Quail have also been used in sexual conditioning studies illustrating how natural stimuli predict successful reproduction via Pavlovian processes. In addition, they have proven to be a good model to study how variation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
81
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 137 publications
(201 reference statements)
1
81
0
3
Order By: Relevance
“…Moreover, the correlation coefficient between area of cloacal gland with testicular size, testosterone level and fertility percent was found to be high and ascertained statistically (Biswas et al, 2007). Hence, cloacal gland area provides an external statistic for the quality of androgen status in the male quails during sexual maturation (Ball and Balthazart, 2010).…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, the correlation coefficient between area of cloacal gland with testicular size, testosterone level and fertility percent was found to be high and ascertained statistically (Biswas et al, 2007). Hence, cloacal gland area provides an external statistic for the quality of androgen status in the male quails during sexual maturation (Ball and Balthazart, 2010).…”
Section: Discussionmentioning
confidence: 88%
“…Also a high degree of correlation was established between the area of cloacal gland with testicular size (Follett and Maung, 1978), testosterone level (Mohan et al, 2002) and fertility (Biswas et al, 2007). Hence, it provides an external marker of the circulating androgen (Ball and Balthazart, 2010). However, after discontinuing DEX administration on day 14 of the experimental period it was found that both body weight and cloacal gland area of male quail recovered to the normal levels within 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The present review presents a synthesis of recent work carried out in our laboratory on the acute control of male sexual behaviour by brain-derived oestrogens and on the mechanisms that control their local synthesis by aromatase. These studies were conducted in Japanese quail, capitalising on the abundance of brain aromatase expressed in the avian brain (compared to mammals) and the tight regulation of reproductive behaviour by steroids in this species (17).…”
mentioning
confidence: 99%